Pengaruh ROA, ROE, dan EPS terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020 - Yuni Mayanti (Jurnal Accounting Information System (AIMS), 2022)
The capital market in Indonesia can be an alternative for people to invest. One of them is investing in stocks. However, in investing in stocks, investors should have information related to the dynamics of stock prices before choosing and investing their funds in the company. There are two analyzes in determining the right stock, that is fundamental analysis and technical analysis. One of the fundamental analysis in making investment decisions using profitability ratios. The profitability ratios used in this study are Return on Assets (ROA), Return on Equity (ROE) and Earning Per Share (EPS). The purpose of this study was to determine the effect of Return on Assets, Return on Equity and Earning Per Share on stock prices in banking companies listed on the Indonesia Stock Exchange in 2017-2020. The author conducted research for the years 2017 – 2020. The population used was 45 banking companies and the sample set was 10 companies with certain criteria using purposive sampling as the sampling technique. The research method uses descriptive research with a quantitative approach. The data analysis technique used multiple linear regression. The results in this study explain that Return On Assets partially has a positive and insignificant effect on banking stock prices listed on the Indonesia Stock Exchange, Return On Equity partially has a negative and insignificant effect on banking stock prices. listed on the Indonesia Stock Exchange, Earning Per Share partially has a positive and significant influence on the price of banking shares listed on the Indonesia Stock Exchange, Return On Assets, Return On Equity and Earning Per Share simultaneously have a significant effect on the stock price of banking.